Comparative spectrophotometric determination of 3-hydroxyflavone based on zinc and aluminium complexes and their antioxidative profiles - Pavun Leposava; Janošević-Ležaić Aleksandra; Uskoković-Marković Snežana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2024)
Flavonoids, as plant-derived compounds, were essential active components in traditional medicine for centuries. Their potential or confirmed effects include antiviral, antimutagenic, antiinflammatory, antibacterial, vasodilatory, and anticancer properties. The promotion of a plantbased diet, along with the benefits of consuming flavonoids, has recently become increasingly attractive. 3-Hydroxyflavone (3HF) is the structural spine of flavonols, an important subgroup of flavonoids. Although 3HF itself does not exist in plants per se, it exerts many of its effects because of its characteristics that allow it to prevent free radical generation. This work is focused on the characterization of 3HF complexes with zinc(II) and aluminium(III) ions (Zn-3HF and Al-3HF, respectively). Besides this, a simple, fast, and low-priced spectrophotometric method for 3HF determination, with very low LOD and LOQ, based on Zn-3HF and Al-3HF formation, was established. A slight advantage is given to the modification with Al3+ ion on pH 4.91, due to very low LOD and LOQ values of 1.83×10-7 molL-1 , and 5.50×10-7 molL-1 , respectively, and a high correlation coefficient, R =0.99986. Furthermore, the antioxidant ability of Zn-3HF, Al-3HF, and parent 3HF was examined by the ABTS and DPPH tests. They brought the Zn-3HF complex to the fore as a potential antioxidative agent.